Manufacturing possibilities creative action and industrial recomposition in the United States, Germany, and Japan - Herrigel, Gary. (Oxford : Oxford University Press, 2010)
'Manufacturing Possibilities' examines adjustment dynamics in the steel, automobile and machinery industries in Germany, the U.S., and Japan since World War II. Using detailed historical and interview based contemporary analysis, the book looks at how national industrial actors in each sector try to compete in global markets.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Sept. 7, 2010).
Keywords: Manufacturing industries -- Germany; Manufacturing industries -- United States; Manufacturing industries -- Japan; Germany -- Foreign economic relations; United States -- Foreign economic relations; Japan -- Foreign economic relations; Structural adjustment (Economic policy) -- Germany; Structural adjustment (Economic policy) -- United States; Structural adjustment (Economic policy) -- Japan